Study on the Development of Diltiazem HCl Loaded Colonic Drug Delivery Systems (CDDS) Using Various Polymers and Characterization of their Release Profiles by In Vitro Dissolution Studies - Islam, Muhammad Sahidul; Chowdhury, Jakir Ahmed; Tania, Shirajum Monira (Dhaka University Journal of Pharmaceutical Sciences, 2011)
This investigation describes the preparation and in vitro evaluation of Colonic Drug Delivery of Diltiazem HCl tablet. Methocel K 4M premium, Methocel K 100M premium CR, Methocel K 15M CR and Xanthan gum were used for release controlling properties. For this purpose, tablets containing 90 mg of Diltiazem HCl along with different amounts of the aforementioned polymers were prepared using direct compression technique. All the formulations were then evaluated for thickness, hardness, diameter, weight variation and in vitro drug release characteristics as per USP monograph. Tablets prepared were placed in a basket type dissolution apparatus containing HCl solution (pH-1.2) for the first 2 hours and phosphate buffer (pH-7.4) for the next 6 hours of the study. The amount of drug released was determined at 237nm by a UV-visible spectrophotometer. Fitting of release data to different kinetic models showed that Methocel K 4M premium containing matrices conformed based to Korsmeyer release kinetics, Methocel K 100M CR based matrices to Korsmeyer and zero order, Methocel K 15M CR based matrices to zero order kinetics and Xanthan gum containing tablets to either of Higuchi and Korsmeyer release kinetics. The release exponent (n) derived from Korsmeyer-Peppas equation for the studied formulations implied that the release of Diltiazem HCl from Methocel K 4M premium based matrices and Methocel K 100M CR based formulations was Super case II transport mechanism. The value of release exponent (n) for Methocel K 15M CR containing matrices was mainly governed by Super case II transport. Xanthan gum based formulations was Anomalous/ Non-Fickian. Briefly, Methocel K 15M CR was found to be suitable for sustaining the release of Diltiazem HCl from matrix formulation inside the colon. Key words: Colonic Drug Delivery; Direct Compression; Methocel K 4M premium; Methocel K 100M CR; Methocel K 15M CR; Xanthan gum. DOI: 10.3329/dujps.v9i1.7424 Dhaka Univ. J. Pharm. Sci. 9(1): 7-13, 2010 (June)